Digital Wallet Public Policy - Nutjamrat, Donyakorn; Phuengpha , Noppawan (Universitas Muhammadiyah Sidoarjo, 2024)
The burgeoning integration of digital wallets into daily financial transactions signals a pivotal shift in monetary policies worldwide. This paper examines the role of digital wallets in shaping public policy, focusing on their capacity to streamline transactions, enhance financial inclusion, and stimulate economic activities. By analyzing policies from various countries, including China and Japan, the study aims to uncover the underlying factors that contribute to the success or failure of these digital tools. The research employs a quantitative approach to evaluate the economic impacts of digital wallets, considering multiple variables such as transaction volume, user demographics, and access to banking services. The findings suggest that supportive government policies, robust infrastructure, and strategic collaborations with private sectors are critical for maximizing the benefits of digital wallets. The study contributes to the broader understanding of digital finance, offering actionable insights for policymakers aiming to optimize digital wallet frameworks for economic growth and societal benefit.